PERSEPSI WAJIB PAJAK TERKAIT LOVE OF MONEY, MACHIAVELLIAN, DAN EQUITY SENSITIVITY PADA ETIKA PENGGELAPAN PAJAK - Esther Dwitia, (2020)
This study aims to determine the effect of love of money, machiavellian, and equity sensitivity on tax evasion ethics of taxpayers. The population of this research is individual taxpayers who are obliged to tax return and are registered in KPP Pratama in Jakarta, Bogor, Tangerang and Bekasi (Jabotabek) areas. The sample was collected by snowball sampling method. The data used in this study are primary data by using questionnaire with 100 respondents as individual taxpayers. The data was collected from May 4, 2020 to May 23, 2020. Data analysis was performed using Microsoft Excel 2013 and SmartPLS 3.0. The results of this study showed that (1) love of money has an effect on ethics of tax evasion. (2) machiavellian has no effect on ethics of tax evasion. (3) equity sensitivity has no effect on the ethics of tax evasion.